Effect of minimally invasive arthroscopy-assisted acupotomy debridement in the treatment of rheumatoid arthritis of the knee joint - YI, Fang; CHEN, Chengmei; CAO, Jialing; FU, Rong (Chinese Journal of Integrative Nursing, 2021)
Objective To explore the clinical effectiveness of minimally invasive arthroscopy-assisted acupotomy debridement in the treatment of rheumatoid arthritis of the knee joint. Methods Based on inclusion and exclusion criteria, a total of 138 patients with rheumatoid arthritis of the knee were selected and divided into two groups: 69 patients in the control group received conventional drug treatment, 69 patients in the observation group received minimally invasive arthroscopy-assisted acupotomy debridement combined conventional drug treatment. Primary outcomes of intervention were Lysholm knee scale and Visual Analogue Scale (VAS) on pain. Results Lysholm score of the control group was lower than that of observation group after treatment (56. 49±12. 24 vs. 84. 90±12. 71, P<0. 05). The VAS score of the control group was higher than that of observation group after treatment(1. 64±0. 6 vs. 0. 19±0. 39, P<0. 05). Conclusion For patients with rheumatoid arthritis of the knee joint, the minimally invasive arthroscopy-assisted acupotomy debridement on the basis of conventional treatment can achieve short-term pain relief and improve the functional activity of the knee joint, so as to promote the good prognosis of the disease and improve the evaluation of patient prognosis. (目的 探讨累及膝关节的类风湿关节炎患者在常规治疗基础之上联合应用针刀镜治疗的临床有效性。方法 根据纳入排除标准选取膝关节类风湿关节炎患者138例, 依据患者在治疗过程中是否接受了针刀镜治疗, 分为常规药物治疗的对照组以及联合应用针刀镜治疗的观察组。对比分析2组纳入研究指标之间差异是否具有统计学意义。结果 对照组治疗后的Lysholm评分(56. 49±12. 24)分, 低于观察组的(84. 90±12. 71)分, 差异有统计学意义(P<0. 05)。对照组疼痛视觉模拟评分(VAS)(1. 64±0. 64)分, 高于观察组的(0. 19±0. 39)分, 差异有统计学意义(P<0. 05)。结论 针对累及膝关节的类风湿关节炎患者, 在常规治疗基础上联合应用针刀镜治疗可以实现短期疼痛缓解、膝关节功能活动能力提高, 从而实现对疾病良好预后的促进和患者评价的提高。)